2013
DOI: 10.1177/1054773813481801
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Depression in Medication Adherence Among Heart Failure Patients

Abstract: The purpose of the study was to explore the association between depression and medication adherence in heart failure (HF) patients. Studies have shown that people with depression are likely to be nonadherent to their prescribed medication treatment. But other studies suggest that nonadherence may be overestimated by people with depression. A total of 244 adults with Stage C HF completed the study. Self-reported medication adherence was obtained using the Basel Assessment of Adherence Scale (BAAS); objective da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 40 publications
3
35
1
2
Order By: Relevance
“…Depression was also associated with increased delay (36,43) between HF symptom onset and hospital admission, but not with self-reported consultation behavior in another large high-quality study (n = 958) (36). Considering the remaining cross-sectional studies, an association with poor exercise adherence was reported as well (35,44), whereas evidence from other studies was mostly weak, inconsistent, or lacking (16,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). Most associations disappeared when other explaining variables were taken into account, for example, disease severity, social support, or self-efficacy, or when it was assessed with a more objective method (46).…”
Section: Emotional Determinants Of Hf Self-carementioning
confidence: 88%
See 1 more Smart Citation
“…Depression was also associated with increased delay (36,43) between HF symptom onset and hospital admission, but not with self-reported consultation behavior in another large high-quality study (n = 958) (36). Considering the remaining cross-sectional studies, an association with poor exercise adherence was reported as well (35,44), whereas evidence from other studies was mostly weak, inconsistent, or lacking (16,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). Most associations disappeared when other explaining variables were taken into account, for example, disease severity, social support, or self-efficacy, or when it was assessed with a more objective method (46).…”
Section: Emotional Determinants Of Hf Self-carementioning
confidence: 88%
“…Considering the remaining cross-sectional studies, an association with poor exercise adherence was reported as well (35,44), whereas evidence from other studies was mostly weak, inconsistent, or lacking (16,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). Most associations disappeared when other explaining variables were taken into account, for example, disease severity, social support, or self-efficacy, or when it was assessed with a more objective method (46). Intriguingly, only minor but not major depression based on a clinical interview was associated with poor HF self-care in one study possibly indicating a nonlinear relationship (15).…”
Section: Emotional Determinants Of Hf Self-carementioning
confidence: 97%
“…Many patients with chronic diseases have concurrent depression. Depression is associated with poor treatment compliance, and some researchers consider that this may be an important factor for the failure of BFT in some patients [48][49][50]. In addition, patients with depression have autonomic nervous dysfunction; low vagal tone can result in decreased gastrointestinal motility [51].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, there are several reasons why an effective laboratory genomic discovery may not be translated as an effective clinical therapy. Reasons include cognitive impairment and depression [41] , asymptomatic disease [42] , side effects of the medication, which in the case of aging are likely to be several because a wide range of therapeutic interventions will have to be deployed [43] , complexity of the therapeutic approach [44,45] and even administrative issues (including inadequate follow-up or discharge planning, poor relationship between patient and provider, missed appointments, lack of health insurance, and cost) [46] . Each of these reasons in isolation, may not be sufficiently considered as a significant obstacle.…”
Section: One Example: Non-adherencementioning
confidence: 99%